Synthesis, mechanical, and flammability properties of metal hydroxide reinforced polymer composites: A review - Mochane, Mokgaotsa J.; Mokhothu, Thabang Hendrica; Mokhena, Teboho Clement (Polymer engineering and science, 2022)
Burning of plastics present a serious problem for both our health and safety when applied in advanced applications. Based on the above argument, there is need to enhance the flammability resistance of polymers in order to meet the required flammability standards. Various flame‐retardant fillers are incorporated into polymers in order to provide a protection against heat into the system and inhibit the diffusion of volatile materials out of the polymer composite system. Different flame‐retardant fillers including phosphorus‐based materials, carbon‐based flame retardants, and inorganic hydrated flame‐retardant fillers have been added into polymers in order to improve the flame retardancy of the plastics. Amongst the abovementioned flame‐retardant fillers, inorganic hydrated fillers have gained popularity, especially magnesium hydroxide (Mg(OH)2) due its high heat absorption capacity, less smoke release, and non‐toxic, as a result environmentally friendly flame‐retardant filler. However, an effective content of magnesium hydroxide for better flammability retardancy is approximately 60 wt%, which happens to deteriorate the mechanical properties of the magnesium hydroxide/polymer composites. In order to try and compensate for reduction in mechanical properties and improve the flame retardancy of the composites at the same time, magnesium hydroxide is incorporated with another flame‐retardant fillers. This review article covers an in‐depth discussion on the effect of magnesium hydroxide modification, synergistic effect with other fillers, particle size of the magnesium hydroxide, and the effect of compatibilizer(s) on both mechanical and flammability properties of magnesium hydroxide reinforced polymer composites.